"En Caul" caesarean delivery for multiple pregnancy - Zainon, Nur Zawani; Ismail, Hamizah; Ismail, Nurul Jannah; Abdul Rashid, Nurul Nafizah; Abd Malik, Nur Rashidah (Malaysian Medical Association, 2023)
Introduction: Caesarean delivery of a severely premature fetus came with a risk of traumatic delivery due to drastic uterine contraction upon rupture of the membrane, the so called “hug-me-tight-uterine”condition. Added by the fragile fetal skin and the surgeon’s anxious hands. It is imagined to be worse with two babies. Case Description: This is a video presentation of a case series for multiple pregnancies delivered through “En Caul” caesarean that managed to prevent traumatic delivery to the premature babies. First case of a 33-week gestation, MCMA twin. Second case of MCDA twin at 26 weeks gestation and last case DCDA twin at 32 weeks of gestation. The MCMA and MCDA were delivered by full “En Caul” and DCDA case delivered with partial (first twin) and full (second twin) “En Caul” caesarean. The drastic uterine contraction was not seen in all three deliveries. Conclusion: Mothers were all under spinal anaesthesia and did not require uterine relaxant agent. Post deliveries all babies did not sustain any trauma and mothers had no post-partum haemorrhage or extended uterine tear. Conclusion: “En Caul” caesarean delivery is a safe procedure for pre-term multiple pregnancies and that one should consider especially for the MCMA.